Analysis of Students' Multiple Intelligences in Biology Learning Activities - Vera Lisnawaty Manik; Idha Nurhayati (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The research objective was to determine the multiple intelligences of students in biology learning activities for class XII IPA at SMA Negeri 1 Sarolangun Regency. Methodology: The design used in this research is a descriptive analytic research design. The number of samples in this study were 40 students. The types of data in this study are quantitative and qualitative. The method of collecting data in this study is by interviewing and documentation. Main Findings: In the Linguistic intelligence indicator, the percentage reached 76.15% in the high category, Mathematical-Logical intelligence reached 75% in the medium category, Visual-Spatial intelligence reached 71% in the medium category, Kinesthetic intelligence reached 67.5% in the medium category, Musical intelligence reached 59% in the high category, Interpersonal intelligence reaches 67.5% in the medium category, Intrapersonal intelligence reaches 74.15% in the medium category, and Naturalist intelligence reaches 81.5% in the high category. Novelty/Originality of this study: Provide reference material that can be used as material for consideration in developing learning strategies and tools in carrying out learning activities.